Beginner teachers and the challenges of the tenure exams: A longitudinal zonal analysis of official data from pre-secondary education - Kiru, Ramona (IJRDO- Journal of Educational Research, 2020)
The Tenure Exam is an important challenge for all beginner teachers in Romanian education. The resumption of this exam has become a habit of the first years of teaching, clearly influencing the evolution of the regional results. The 147 subjects of the research represent the entire population that took this exam only once during the years 2015-2019, in Ilfov county, to occupy a teacher position in the preschool or primary education.The evolution of the results during the period examined is positive, the differences between the obtained averages being statistically significant. There are no significant differences between teachers depending on the level of education, the area of residence, the level of education, the type or form of education completed. Both the increase in the number of graduates who want to work in education, as well as the increasing marks registered to the Tenure Exam indicate that the teacher positions are beginning to be attractive to the labor market.Further research should probe the relationship between the grade obtained to the Tenure Exam and the ability of beginner teachers to cope well with the first years of teaching. Also, the subsequent research should focus on identifying the special needs of the pre-secondary education in this area and on offering specific educational programs for the initial training of the teachers who will teach in this area.